Cyanobacterial biomass as n-supplement to oil palm empty fruit bunch (opefb) fibre for improvement of cellulase production by Aspergillus terreus in submerged fermentation. - Shariarinour, Mahdi; Abd Wahab, Mohd. Noor; Mohamad, Rosfarizan; Mustafa, Shuhaimi; Ariff , Arbakariya (North Carolina State University, 2011)
The possibility of using dry biomass of a cyanobacterium, Anacystis nidulans, as nitrogen source supplement for improvement of cellulase production by Aspergillus terreus was studied in submerged fermentation using oil palm empty fruit bunch (OPEFB) fibre as a carbon source. For comparison, four other nitrogen sources (ammonium sulphate, urea, peptone, and yeast extract) were also tested. Growth and cellulase production were greatly enhanced in fermentation using biomass of cyanobacterium as the nitrogen source. The use of cyanobacterial biomass as a nitrogen source also reduced the inhibitory effect of high concentrations of CaCl2 to growth of A. terreus and cellulase production. The addition of 0.3 g L-1 CaCl2 to the medium containing OPEFB fibre and cyanobacterial biomass further enhanced the cellulase production, though growth remained unchanged. The final FPase, CMCase, and β-glucosidase obtained in fermentation using 10 g L-1 OPEFB fibre and 6 g/L cynaobacterial biomass with the addition of 3 mM CaCl2 was 0.97 U mL-1, 14.1 U mL-1, and 10.4 U mL-1, respectively.